Hubungan Antara Perilaku Pengolah dan Pengembangan Agribisnis Sagu di Kabupaten Konawe Selatan - Darlis Darlis; Weka Widayati; Ilma Sarimustaqyma Rianse (Jurnal Sosio Agribisnis, 2020)
Sago is a source of food for some people in Southeast Sulawesi, where one of the distribution areas is in South Konawe Regency. This study aims to: determine the behavior of the processing and development of sago agribusiness, and to analyze the relationship between processing behavior and the development of sago agribusiness. The population in this study was the sago processing group. Sampling was done randomly, with a total sample of 64 processing groups. The study variables consisted of sago processing behavior (knowledge, skills, attitudes) and sago agribusiness development (internal factors and external factors). Data were analyzed descriptively and analyzed using the Spearman rank correlation test. The results of the study show that: the behavior of sago processors from the aspects of knowledge and attitude is in the medium category, while from the skills aspect it is in the high category. The behavior of sago processing and sago agribusiness development has a positive relationship with moderate criteria.Keywords: sago processing behavior, agribusiness development, positive relationship